2021
DOI: 10.3390/microorganisms9122568
|View full text |Cite
|
Sign up to set email alerts
|

The Human Vulvar Microbiome: A Systematic Review

Abstract: The link between cancer and the microbiome is a fast-moving field in research. There is little knowledge on the microbiome in ((pre)malignant) conditions of the vulvar skin. This systematic review aims to provide an overview of the literature regarding the microbiome composition of the healthy vulvar skin and in (pre)malignant vulvar disease. This study was performed according to the PRISMA guidelines. A comprehensive, electronic search strategy was used to identify original research articles (updated Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 83 publications
(117 reference statements)
0
7
0
Order By: Relevance
“…It was of significance to demonstrate the effect of the vaginal microbial environment in the physiological process and pathological process in the female reproductive system. It was reported [ 24 , 25 ] that there are significant differences in vaginal microbiome between cancer microenvironment and noncancer microenvironment women, but less studies reported the mechanisms among these associations. In this study, we explore the effect of Peptostreptococcus anaerobius on macrophage polarization and further angiogenesis and also explore the certain mechanisms of these effects.…”
Section: Discussionmentioning
confidence: 99%
“…It was of significance to demonstrate the effect of the vaginal microbial environment in the physiological process and pathological process in the female reproductive system. It was reported [ 24 , 25 ] that there are significant differences in vaginal microbiome between cancer microenvironment and noncancer microenvironment women, but less studies reported the mechanisms among these associations. In this study, we explore the effect of Peptostreptococcus anaerobius on macrophage polarization and further angiogenesis and also explore the certain mechanisms of these effects.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the microbial community depended on the physiological state of the skin, and the relative abundance of bacteria changed with different humidity and sebaceous microenvironments. The vulva microbiota is diverse, and the normal vulva microbiota includes the characteristics of the vagina, urethra, and colon ( Brown et al, 2007 ; Pagan et al, 2021 ). Previous studies on the vulvar skin microbiota, from cultivation to culture-independent molecular techniques, have shown that Lactobacillus and Corynebacterium spp., as well as Staphylococcus aureus and Prevotella, were the main bacterial components of healthy vulvar skin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that colonization and alteration of the skin microbiota are associated with a variety of skin diseases, such as dermatitis, rosacea, and psoriasis ( Holmes et al, 2013 ; Nakatsuji et al, 2017 ; Thio et al, 2018 ; Wang et al, 2020 ). Currently, microbiome profiling has been used to explore the microbial composition of the vulvar skin and the role of the microbiome in vulvar health and disease ( JayaramA et al, 2014 ; Pagan et al, 2021 ; Murina et al, 2020 ). However, few studies have focused on the correlation between vulvar skin microbiota and VLS.…”
Section: Introductionmentioning
confidence: 99%
“…After excluding duplicate articles, two researchers assessed the quality of the included studies separately and critically based on the Joanna Briggs Institute checklist developed for cross-sectional studies ( 26 ). Rintala et al ( 27 ), Ogutu et al ( 28 ), and Pagan et al ( 29 ) demonstrated that it is a valuable tool for testing and assessing the quality of observational studies. This checklist consists of eight straightforward questions covering topics such as sample inclusion criteria, study population and setting details, validity and reliability, measurement criteria for conditions, confounding variables, and statistical analyses ( 27 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Rintala et al ( 27 ), Ogutu et al ( 28 ), and Pagan et al ( 29 ) demonstrated that it is a valuable tool for testing and assessing the quality of observational studies. This checklist consists of eight straightforward questions covering topics such as sample inclusion criteria, study population and setting details, validity and reliability, measurement criteria for conditions, confounding variables, and statistical analyses ( 27 29 ). Answers to each question include Yes, No, Unclear, and Not applicable.…”
Section: Methodsmentioning
confidence: 99%